2016
DOI: 10.1007/s00381-015-2999-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival of an infant with an atypical teratoid/rhabdoid tumor following subtotal resection and low-cumulative dose chemotherapy: a case report

Abstract: This case report highlights that independent prognostic factors are urgently needed for optimizing treatment stratification and preventing overtreatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In vitro studies have elucidated a multitude of affected pathways and mechanisms as a consequence of SMARCB1 loss in RT, unveiling new potential therapeutic targets. This includes among others the overexpression of Aurora Kinase A, 31,32 upregulation of EZH2, 33 as well as CDK4/CDK6/cyclin D1/RB pathway activation 34,35 and many more. 36 Translation of these findings into clinical trials has been challeng- reported single cases of responses to metronomic chemotherapy regimens in ATRT using either vinorelbine, cyclophosphamide, and celecoxib or in the latter bevacizumab, liposomal cytarabine, celecoxib, cyclophosphamide, and etoposide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies have elucidated a multitude of affected pathways and mechanisms as a consequence of SMARCB1 loss in RT, unveiling new potential therapeutic targets. This includes among others the overexpression of Aurora Kinase A, 31,32 upregulation of EZH2, 33 as well as CDK4/CDK6/cyclin D1/RB pathway activation 34,35 and many more. 36 Translation of these findings into clinical trials has been challeng- reported single cases of responses to metronomic chemotherapy regimens in ATRT using either vinorelbine, cyclophosphamide, and celecoxib or in the latter bevacizumab, liposomal cytarabine, celecoxib, cyclophosphamide, and etoposide.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have elucidated a multitude of affected pathways and mechanisms as a consequence of SMARCB1 loss in RT, unveiling new potential therapeutic targets. This includes among others the overexpression of Aurora Kinase A , 31,32 upregulation of EZH2, 33 as well as CDK4/CDK6/cyclin D1/RB pathway activation 34,35 and many more 36 …”
Section: Discussionmentioning
confidence: 99%